The trouble with mummies - Hitchcock, Fleur (Hot Key Books, 2013)
Sam comes home one day to find his family turning a little bit loopy -- his mum is redecorating using hieroglyphics and his dad is building a pyramid in the back garden. He hopes it's just a weird new fashion ...but then the strangeness starts to spread. People are turning into Egyptians everywhere!